2019
DOI: 10.15439/2019f284
|View full text |Cite
|
Sign up to set email alerts
|

Playing the Sprint Retrospective

Abstract: In this paper, we report on a replication of the study by Przybylek & Kotecka [2017]. The aim of our study was to revise the work practices related to Sprint Retrospectives in Bluebay Polska Sp. z.o.o. by adopting collaborative games. The feedback received from two Scrum teams confirms the findings from the original study and indicates that collaborative games improve participants' creativity, involvement, and communication as well as produce better results than the standard retrospective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Przybyłek & Kotecka [22] adopted 5 retrospective games, which improved team members' creativity, involvement, and communication as well as produced better results than the standard retrospective. In our previous work [15,25], we confirmed their findings, while this paper complements and extends this research area.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Przybyłek & Kotecka [22] adopted 5 retrospective games, which improved team members' creativity, involvement, and communication as well as produced better results than the standard retrospective. In our previous work [15,25], we confirmed their findings, while this paper complements and extends this research area.…”
Section: Introductionsupporting
confidence: 85%
“…We also concluded that the Sprint Retrospective should be fixed first. Accordingly, in the first cycle, we planed to implement all retrospective games that we used in our prior study [25] and in addition try a new game, namely Mountain Climbing. Besides, we decided to implement each game twice, first in non-anonymous and then in anonymous way.…”
Section: B Action Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrospective stage of an agile sprint is a critical component of the scrum methodology for creating, delivering and managing complex projects. Its goal is to identify the achievements and mistakes of the previous sprint and to connect the resulting experience to action suggestions for improvement [19].…”
Section: Scrummentioning
confidence: 99%